"#Literate Lives Matter": Black Reading, Writing, Speaking, and Listening in the 21st Century. (November 2016) - Ladson-Billings, Gloria
Literacy for African Americans has never been merely about skill development and text comprehension. Its primary purposes and foci have been liberation, empowerment, and self-determination. From slave narratives to contemporary liberation movements assisted by social media, African Americans have deployed literacy strategically to as Paulo Freire says, "to read the word and the world." This lecture draws on the author's family and personal history along with her research career to illustrate that "literate lives matter!"